Impact of Migration in Marriage Rituals of Bharseli Magar of Kathmandu Valley - Budhathoki , Hemanta (Patan Prospective Journal, 2024)
This study related to migration and marriage rituals of the Bharseli Magar of Kathmandu valley consists of 92 households of Bharseli Magar of Kathmandu Valley. This study is completed by using an interview schedule and the Key Informant Interview (KII) method. The objective of this paper is to study the impacts of migration on the marriage ritual of the Magar community and this study explains about present practice of the marriage ritual of the Bharseli Magar. The traditional ritual of Magar community of Bharse, Gulmi is cross-cousin marriage. Especially in Bharse of Gulmi three sub-clans of Magars have practiced the marriage system clockwise. However due to the excessive migration process, the migrated Bharseli Magars rarely follow the cross-cousin marriage system and three sub-clan marriage systems in the present context. In this paper how migration contributes to change in marriage rituals of the Magar community has been explained. Due to migration, especially, food items of Sagun of Magani, Sodhani, Theki, Dhogbhet, Dulhan Farkaune, etc. have been changing. The place of traditional marriage of Bharseli Magar of Kathamandu valley was houses. Due to modernization, globalization, and urbanization marriage/wedding parties are mostly organized in party palaces. In addition, there is change in items of ornaments, clothes and other aspects.